2020
DOI: 10.3390/s20082261
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Optical Wireless Communications: Overview

Abstract: Underwater Optical Wireless Communication (UOWC) is not a new idea, but it has recently attracted renewed interest since seawater presents a reduced absorption window for blue-green light. Due to its higher bandwidth, underwater optical wireless communications can support higher data rates at low latency levels compared to acoustic and RF counterparts. The paper is aimed at those who want to undertake studies on UOWC. It offers an overview on the current technologies and those potentially available soon. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(62 citation statements)
references
References 131 publications
0
44
0
1
Order By: Relevance
“…Comment: Due to the comprehensiveness and wide-ranging scope, this chapter outlines just part of the advancements in OC leaving issues such as underwater OC [19] and Machine learning for OC [1] out of scope.…”
Section: Discussionmentioning
confidence: 99%
“…Comment: Due to the comprehensiveness and wide-ranging scope, this chapter outlines just part of the advancements in OC leaving issues such as underwater OC [19] and Machine learning for OC [1] out of scope.…”
Section: Discussionmentioning
confidence: 99%
“…In [30], they evaluated the continuous-variable quantum key distribution method over an underwater link by using MC simulation. They showed that the performance evaluated by MC simulation is more accurate due to considering the contribution of scattered photons and the system transceiver parameters compared to Beer's law which depended on wavelength and distance [31]. In [19], the channel capacity for various link distances, water types, and transceiver parameters were evaluated using MC simulation, and it was shown that the UOWC bandwidth for the clear, coastal, and harbor waters are in the order of hundreds of MHz, tens of MHz and MHz, respectively.…”
Section: Uowc Channel Modelmentioning
confidence: 99%
“…These include slow propagation speed, limited bandwidth, energy constraints, node mobility with water current, and high deployment costs. UWSNs are significantly different from terrestrial (radio) sensor networks as they utilize acoustic waves with comparatively lower loss and longer range in the underwater environment than electromagnetic and optical waves [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Related Workmentioning
confidence: 99%